Compact modelling of a spin-orbit torque logic device - Chua, Daniel Chenhao (Nanyang Technological University, 2019)
A compact model of a device is a model which captures the essential physics of the device while still being simple enough to be implemented in a circuit simulator. The compact modelling of spintronic devices is essential in the effort to integrate them into large scale electronic systems. This is because it allows for the prototyping of circuit designs which involve the interfacing of spintronic and conventional charge-based electronic devices. In this project, a compact model of a Spin-Orbit Torque (SOT) driven multilayer device is developed. The development of the compact model involved translating the essential physics of the device into circuit analogs which were then implemented as modules in LTSpice, a circuit simulator. These modules were then used to create a circuit simulator-compatible model of the multilayer device. Numerical characterization of the compact model showed good agreement with a standard analytical result for the critical switching current of a Spin Hall Effect Spin-Torque (SHE-ST) driven bilayer device with perpendicular magnetic anisotropy (PMA). The compact model was then used to design a device which exhibits reconfigurable logic functionality. The logic reconfigurability was demonstrated via circuit simulation.